PENGARUH PENGUNGKAPAN CSR TERHADAP PELAPORAN PAJAK AGRESIF, DAN PENGARUHNYA TERHADAP RETURN SAHAM - Anis, Idrianita (Jurnal ASET (Akuntansi Riset), 2017)
Abstract. This study examine the association between Corporate Sosial Responsibility (CSR), corporate tax-aggressiveness and stock return. It also examine moderating effect of the effectiveness of audit committee as corporate governance mechanism to the association of CSR disclosure to corporate tax-aggressiveness. Examination conducted on 173 firm-years that were selected by purposive sampling method from manufacturing firm listed at IDX from 2011-2013. By measuring the corporate tax-  aggressiveness through 4 measures: Effective Tax Rates (ETR), Cash-ETR, Book-Tax Difference (BTD), Abnormal-BTD, the result showed that CSR disclosure weakly effected corporate tax agresiveness. Study found CSR disclosure negatively effected Cash-ETR, and there were no significant effect to other three measure ETR, BTD and AB_BTD. The result shown there were no significant effect of audit committee effectiveness to corporate tax aggressiveness. The result also showed that there were no significant effect of CSR disclosure and audit committee effectiveness to stock return, but corporate tax agresive information have  significant influence to stock return. Keywords: corporate social responsibility; effective taxes rates; cash effective taxes rate; book-taxes difference; abnormal book-taxes difference and stock returnAbstrak. Studi ini menguji hubungan antara pengungkapan Corporate Social Responsibility (CSR) dan pelaporan pajak agresif dan return saham. Studi juga menguji pengaruh moderasi dari variabel efektifitas komite audit sebagai mekanisme corporate governance dalam hubungan pengungkapan CSR terhadap pelaporan pajak agresif. Pengujian dilakukan menggunakan sampel  yang dipilih menggunakan metode purposive sampling, dari perusahaan manfaktur terdaftar di Bursa Efek Indonesia dari 2011-2013. Dengan menggunakan pengukuran pajak agresif 4 ukuran yaitu: Effective Tax Rates (ETR); Cash-ETR;  Book-Tax Difference (BTD); Abnormal-BTD;hasil menunjukkan hasil pengungkapan CSR berpengaruhi pelaporan pajak agresif dengan pengaruh yang lemah. Secara spesifik pengungkapan CSR bepengaruh negative terhadap Cash-ETR dan tidak terdapat pengaruh signifikan terhadap ketiga pengukuran pajak agresif yang lainnya yaitu ETR, BTD dan AB_BTD. Hasil menunjukan tidak terdapat pengaruh signifikan antara pengungkapan CSR dan efektifitas komite audit terhadap return saham, namun informasi pelaporan pajak agresif memiliki pengaruh signifikan terhadap return saham.Kata Kunci: tanggung jawab sosial perusahaan, tarif pajak yang efektif; tarif pajak tunai yang efektif; perbedaan buku pajak; buku pajak abnormal.